Revolution and Change in Central and Eastern Europe : Revised Edition. - East, Roger (History and Politics in the 20th Century: Bloomsbury Academic., 2016)
"This comprehensive reference, an expanded edition of Revolutions in Eastern Europe, provides a general introduction and broad historical background of Eastern and Central European countries from the First World War onwards, focusing on the development of independent countries and the establishment of Soviet-backed dictatorships, as well as their subsequent experience of political pluralism and external relations and alignments in post 1989 Europe. Each country is covered in an individual chapter, giving a factual account of their revolutions and upheavals and an assessment of their underlying causes."--Bloomsbury Publishing